Quantificação de carbono sequestrado em sistema de cultivo da cana-de-açúcar em aleias - Silva, Marco Rogerio Gomes da (Universidade Federal de São Carlos, 2012)
The present work aims to analyze the system of alleys, planting trees in rows associated with a commercial crop, in this case sugar cane, with three species of plants with timber characteristic, fertilize and fixative, making nutrient cycling, reducing the monoculture effects, with ecological and environmental gains. This technique will allow the increase of profits per hectare by fixing carbon during the growth period of these trees, besides the sale of wood production and promote the environmental sustainability of sugar cane. The physical parameters used to evaluate were monthly measurements during the first 2 years of experiment established, base diameter and the first branch plus the height of the stem of each plant, to thereby obtain the volume of each plant, to quantify the fixed carbon by non-destructive method. The results showed that the Guapuruvu capture media 685 g / plant of carbon, representing more 1.8 times than Cedar (381 g / plant) and 4.75 times more than Ipê (144 g / plant) in the same period. The Guapuruvu showed a yield higher than the Cedar and Ipe Yellow, both in tree growth and carbon fixation in evaluate period. The Arboreal species did not affect the development of the culture of sugar cane in the bands 30 and 45 meters of cultivation, only in 60 meters there was interference.
Measurement of carbon sequestration farming system of cane sugar in alleys
Keywords: Agroecologia; Aleias; Carbono - fixação; Canade- açúcar; Sustentabilidade; Bens e serviços ambientais; CIENCIAS AGRARIAS